Coronavirus Disease 2019 (COVID-19) Crisis: Losing Our Immunity When We Need It the Most - Abdelaziz Ghanemi; Mayumi Yoshioka; Jonny St-Amand (Biology, 2021)
The ongoing coronavirus disease 2019 (COVID-19) crisis has led to a new socioeconomic reality with the acquisition of novel habits. Measures imposed by governments and health authorities such as confinement and lockdown have had important consequences, including mental health problems, economic crisis, and social isolation. Combined with newly acquired habits such as hand washing, sanitization, and face masks, these have all directly and indirectly led to reduced immunity. Such effects on the immune system not only impact the epidemiological profile with respect to COVID-19 and other infectious diseases but also limit the efficacy of the ongoing anti-COVID-19 vaccination campaign. Therefore, there is a need to review these approaches and optimize measures towards better population immunity, which is much needed during such an epidemic.